2022
DOI: 10.1186/s12943-022-01620-x
|View full text |Cite
|
Sign up to set email alerts
|

Mutual regulation between N6-methyladenosine (m6A) modification and circular RNAs in cancer: impacts on therapeutic resistance

Abstract: The resistance of tumor cells to therapy severely impairs the efficacy of treatment, leading to recurrence and metastasis of various cancers. Clarifying the underlying mechanisms of therapeutic resistance may provide new strategies for overcoming cancer resistance. N6-methyladenosine (m6A) is the most prevalent RNA modification in eukaryotes, and is involved in the regulation of RNA splicing, translation, transport, degradation, stability and processing, thus affecting several physiological processes and cance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(33 citation statements)
references
References 226 publications
0
33
0
Order By: Relevance
“…Due to the rapid multiplication rate, it is easy for cancer cells to form drug resistance to therapy, which severely weakens the efficacy of treatment. Clarifying the mechanism of how cancer cells form drug resistance can be urgent and valuable for cancer treatment [ 100 ].…”
Section: Mechanisms Of M 6 A-lncrnas Mediated Canc...mentioning
confidence: 99%
“…Due to the rapid multiplication rate, it is easy for cancer cells to form drug resistance to therapy, which severely weakens the efficacy of treatment. Clarifying the mechanism of how cancer cells form drug resistance can be urgent and valuable for cancer treatment [ 100 ].…”
Section: Mechanisms Of M 6 A-lncrnas Mediated Canc...mentioning
confidence: 99%
“…Due to different splicing processes, circRNAs were divided into three main types, including exonic circRNAs (ecircRNAs), exon-intron circRNAs (EIciRNAs), and circular intronic RNAs (ciRNAs) ( 59 ). However, with advances in experimental technology, emerging evidence has indicated that circRNAs are implicated in the occurrence and development of many diseases, such as cancer ( 60 ), cardiovascular disorders ( 61 ), neurological disorders ( 62 ), metabolic disorders ( 63 ), and immunological disorders ( 64 ). The functions of circRNAs are as follows: acting as a sponge of miRNA or competitive endogenous RNAs (ceRNAs), interacting with RNA-binding proteins (RBPs) and mRNAs, regulating transcription or alternative splicing, and protein translation ( 65 ).…”
Section: Circrnasmentioning
confidence: 99%
“…N 6 -methyladenosine (m 6 A) modification is firstly described in 1971 years, which has shown critical roles in mRNA metabolism and become focus recently ( Chen et al, 2022 ; Li et al, 2022 ). Methyltransferase installed the m 6 A modification on mRNA, including methyltransferase-like 3 (METTL3), methyltransferase-like 14 (METTL14), and the Wilms tumor 1-associated protein (WTAP) ( Lin et al, 2022 ; Luo et al, 2022 ). In addition, the m 6 A modification was wiped by demethylase, including obesity-associated protein (FTO) and alkB homolog 5 (ALKBH5) ( Qin et al, 2022 ; Zhai et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%